WACANA KEAGAMAAN SYIAH-SUNNI DALAM MAJALAH TEMPO DAN SUARA HIDAYATULLAH - Dadang S Anshori (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2014)
This study aims to describe the language use as representation of mass media attitudes towards Shia-Sunni conflicts. It employed the qualitative method using Fowler’s critical discourse analysis. The data source was news on Shia-Sunni conflicts in Sampang reported in Tempo and Suara Hidayatullah magazines. The findings are as follows. First, Shia-Sunni conflicts are described in news headings and points of view. Tempo describes the conflicts using the point of view of ‘devil attack’ while Suara Hidayatullah presents them as conflicts of religious understanding. Second, expressions such as ‘belief forcing’, ‘Shia cleansing’, ‘devil attack’, and ‘intolerance’ represent Tempo’s attitudes while expressions such as ‘heretical’, ‘misleading’, ‘hijacking’, ‘deifying something’, and ‘infidel’ represent Suara Hidayatullah’s attitudes. Third, based on the use of vocabulary and sentences, Tempo tends to back the Shia group while Suara Hidayatullah tends to back the Sunni group.